Analysis on the Spatio-temporal Characteristics for Different Types of Strong Winds over Yunnan - Wenqian MA; Huahong LI; Xiaohua CHEN; Ying MIN; Yaosun LI; Yu HE (Gaoyuan qixiang, 2025)
Based on multiple observations， 16778 strong winds with speed equal to or greater than 17 m·s-1 from 125 national meteorological stations over Yunnan from 2013 to 2021 are divided into 8 types： thermal low winds， thunderstorm winds， local winds， cold-air winds， winds before southern trough， winds under 500 hPa westerly jet， typhoon winds and winds after plateau trough.The characteristics of spatio-temporal distribution and wind direction/speed of all types of winds except for the local winds are explored.The most frequent strong winds over Yunnan are thermal low winds， followed by thunderstorm winds.The strong winds are mainly observed over the northwest， central， and eastern parts of Yunnan.Except for thunderstorm winds， the wind directions of strong winds could be determined by the causes of their occurrence.The wind speeds mainly range from level 7 to level 9， and the distribution of wind speeds which are equal to or greater than level 10 shows strong discontinuity.Even though the frequencies of thunderstorm winds and winds before southern trough are less than that of thermal low winds， the two types of winds have a higher ability to cause extremely strong winds.The annual variation of occurring times shows that the winds mainly occur in winter and spring， with the most frequency in March.The annual variation of occurring times of thunderstorm winds shows a bimodal structure with a main peak in April and a sub peak in August.Meanwhile， the annual variation of occurring days of thunderstorm winds also shows a bimodal structure， the occurring days of the sub peak in August are comparable to that of the main peak in April， indicating that thunderstorm winds occurring in spring are relatively organized， while thunderstorm winds occurring in summer are relatively scattered.For the diurnal variation of occurring times， the thermal low winds mainly occur in daytime， with the highest occurring frequency at 15:00 to 15:59 （Beijing time， the same below）.The thunderstorm winds and winds before southern trough mainly occur in afternoon， with the highest occurring frequency at 16:00 to 17:59.The cold-air winds mainly occur from the afternoon to the early morning， with the highest occurring frequency at 18:00 to 19:59.The winds under 500 hPa westerly jet have two periods with high frequencies， afternoon and early morning， and more winds occur in the afternoon.The typhoon winds mainly occur in daytime， with the highest frequency occurring at 16:00 to 17:59.The winds after plateau trough mainly occur in daytime and the beginning of the night， and more winds occur at 15:00 to 16:59.